Elevated maternal serum-free β-human chorionic gonadotropin (β-hCG) and reduced risk of spontaneous preterm delivery*. (2nd October 2019) - Soni, Shelly; Krantz, David A.; Blitz, Matthew J.; Vohra, Nidhi; Rochelson, Burton
Abstract: Objective: To evaluate the relationship between first and second trimester maternal serum-free β-hCG and the risk of spontaneous preterm delivery (PTD). Study design: This was a case-control study of women evaluated and delivered at our institution from 2011 to 2015. Spontaneous PTD was defined as delivery before 37 weeks due to spontaneous preterm labor or premature rupture of membranes. Patient with multifetal gestation and those with medically indicated term or PTD were excluded. Results: Of 877 women meeting the inclusion criteria, 173 delivered preterm and 704 delivered at term, and 8.1% had high free β-hCG in one or both trimesters. High maternal first and/or second trimester free β-hCG (≥95th percentile) was associated with lower rates of PTD. Thirty-two women with high free β-hCG in both first and second trimesters delivered at term. Gestational age at delivery and birth weights were lower in women who did not have high free β-hCG in any trimester. Low free β-hCG (≤5th percentile) in either trimester was not associated with an increased or decreased likelihood of PTD. Logistic regression demonstrated an independent association of high free β-hCG (≥95th percentile) with a reduced likelihood of PTD. Stratified analysis revealed a stronger impact of this association in women with no prior history of PTD. Conclusions: High free β-hCG, in the absence of risk factors for medically indicated PTD, is associated with a reduced likelihood of spontaneous PTD and may represent a marker indicating lower risk.